2020
DOI: 10.1002/aid2.13247
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Helicobacter pylori infection on vitamin D levels in old patients with sarcopenia

Abstract: We aimed to determine the possible relationship between sarcopenia, Helicobacter pylori and 25‐OH vitamin D. A total of 101 patients aged 65 years and over were included in the study, and grouped as sarcopenia (+) and (−) according to the skeletal muscle index (SMI) measured by bioelectrical impedance analysis (BIA). Also, patients were divided into two groups according to the presence and absence of H. pylori infection. There was no significant difference in the frequency of H. pylori infection in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Furthermore, one study conducted in Bahrain highlighted that, for each unit decrease in serum vitamin D level, the risk of H. pylori infection increases by 1.1 [ 25 ]. In a study conducted on an older population with sarcopenia, an inverse relationship between vitamin D deficiency and H. pylori was proposed, suggesting that H. pylori might actually be the risk factor for vitamin D level decrease [ 28 ]. However, Bashir et al proved on a limited population sample that an 8-week supplementation regimen of high oral vitamin D3 doses can significantly decrease H. pylori colonization of the gastric mucosa.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, one study conducted in Bahrain highlighted that, for each unit decrease in serum vitamin D level, the risk of H. pylori infection increases by 1.1 [ 25 ]. In a study conducted on an older population with sarcopenia, an inverse relationship between vitamin D deficiency and H. pylori was proposed, suggesting that H. pylori might actually be the risk factor for vitamin D level decrease [ 28 ]. However, Bashir et al proved on a limited population sample that an 8-week supplementation regimen of high oral vitamin D3 doses can significantly decrease H. pylori colonization of the gastric mucosa.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, future prospective studies and randomized controlled trials are required to clarify the relationship between vitamin D serum levels, its supplementation, and H. pylori, and to evaluate whether the addition of vitamin D3 to therapeutic regimens influences bacterial eradication. Cofounding factors such as age, interfering in the relationship between vitamin D supplementation and H. pylori prevalence and eradication, are also subject to future debate, given the lack of regular vitamin D intake among adult populations and the possible inverse relationship between H. pylori and vitamin D deficiency, as proposed by Bahși et al [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Concerning adults, Shafrir et al demonstrated that vitamin D was inversely related to H. pylori infection and the possibility of infection was significantly higher in vitamin D-deficient patients than vitamin D-sufficient patients [ 105 ]. A recent study similarly reported that in the old patients, aged 65 years, with sarcopenia, H. pylori infection led to vitamin D deficiency and the prevalence of infection was significantly higher in vitamin D-deficient patients [ 106 ]. Twenty years of 1 α -hydroxyvitamin D3 supplementation resulted in a significantly lower H. pylori infection rate in subjects [ 107 ].…”
Section: H Pylori and Vitaminsmentioning
confidence: 99%